Planning, construction and use of handmade simulators to enhance the teaching and learning in Obstetrics - Knobel, Roxana; Menezes, Mariane de Oliveira [UNESP]; Santos, Dbora de Souza; Soligo Takemoto, Maira Libertad [UNESP] (Univ Sao Paulo, Escola De Enfermagem De Ribeirao Preto, 2020)
Objective: to describe the development process and present the results of a pilot study on the use of low-cost handmade simulators for teaching and learning Obstetrics. Method: presentation of 3 low-cost simulators designing, based on educational needs identified in real-world training contexts. The developing process is presented in detail and each simulator was tested and re-tested, being submitted to improvements until their final version. The simulators presented are: delivery simulator shorts, Neoprene uterus for postpartum hemorrhage management, and perineal repair simulator. A pilot study was carried out to evaluate the perception of apprentices through a structured questionnaire, using the Kirkpatrick evaluation model. Data were descriptively analyzed. Results: the respondents (31 apprentices) positively evaluated the simulators, perceiving significant gains in theoretical knowledge, ability to solve clinical problems and decreased anxiety to deal with situations similar to those simulated. Conclusion: low-cost, handmade simulators are feasible and effective, resulting in positive learner evaluations. Their availability as open technology allows the dissemination of their use.
Keywords: Simulation; Obstetrics; Teaching; Teaching Materials; Education; Nursing; Training